Dylematy aspiracji edukacyjnych Polaków - Gucwa-Leśny, Ewa (The dilemmas of Pole's educational aspirations, 2006)
The improvement of educational level is not only the necessary condition of adjustment to Knowledge Based Economy, but also the shortest way to change the way of thinking, needs ans aspirations. The human capital has been appreciated in the general and individual dimension. The Polish society started to be more open and better educated. The improvement of social awareness and protection of science, culture and social dialogue as common good is necessary.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (13); 2006; nr 1127, s. 192-199